PENGEMBANGAN MODUL PEDOMAN GURU DALAM MENDESAIN INSTRUMEN PENILAIAN MATEMATIKA BERBASIS PEMECAHAN MASALAH MATEMATIKA - Antok Kurniawan; Muhammad Rusdi; Jefri Marzal (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to determine the process, specifications, and teacher perception about developing a teacher guide module in making mathematical assessment instruments based on mathematical problem-solving. This research used Research and Development method is used to produce certain products namely the teacher guide module. The development model used in this study is the development model that has been combined from (Marshall, 2009) (Bishopb, 2012) (Rusdi, 2018)became the reference, while in this development research only arrived at producing products and not tested on a student. The steps consist the analysis of problems and needs, literature review, product design, validity, a trial practitioners. The research subjects in this development were two validators consisting of material expert test validators. The type of data taken in this study is qualitative data. The instrument used in the study was an open questionnaire. The stages of the process of developing are (a) Analysis of problems and needs, (b) Literature review, (c) Product design, (d) Validity, (e) Trial of practitioners. The product specifications developed in the module are three chapters on introduction, concepts, and procedures along with examples using the type of problem-solving, namely problem-solving and story problem design. The teacher's perception of the teacher guideline module is positive, from five practitioners recommending that it be used as a guide in making problem-solving questions.